Maternal mental health and infant emotional reactivity: a 20-year two-cohort study of preconception and perinatal exposures. Issue 5 (10th April 2020) - Spry, Elizabeth; Moreno-Betancur, Margarita; Becker, Denise; Romaniuk, Helena; Carlin, John B.; Molyneaux, Emma; Howard, Louise M.; Ryan, Joanne; Letcher, Primrose; McIntosh, Jennifer; Macdonald, Jacqui A.; Greenwood, Christopher J.; et al.
Abstract: Background: Maternal mental health during pregnancy and postpartum predicts later emotional and behavioural problems in children. Even though most perinatal mental health problems begin before pregnancy, the consequences of preconception maternal mental health for children's early emotional development have not been prospectively studied. Methods: We used data from two prospective Australian intergenerational cohorts, with 756 women assessed repeatedly for mental health problems before pregnancy between age 13 and 29 years, and during pregnancy and at 1 year postpartum for 1231 subsequent pregnancies. Offspring infant emotional reactivity, an early indicator of differential sensitivity denoting increased risk of emotional problems under adversity, was assessed at 1 year postpartum. Results: Thirty-seven percent of infants born to mothers with persistent preconception mental health problems were categorised as high in emotional reactivity, compared to 23% born to mothers without preconception history (adjusted OR 2.1, 95% CI 1.4–3.1). Ante- and postnatal maternal depressive symptoms were similarly associated with infant emotional reactivity, but these perinatal associations reduced somewhat after adjustment for prior exposure. Causal mediation analysis further showed that 88% of the preconception risk was a direct effect, not mediated by perinatal exposure. Conclusions: Maternal preconception mental health problems predict infant emotional reactivity, independently of maternal perinatal mental health; while associations between perinatal depressive symptoms and infant reactivity are partially explained by prior exposure. Findings suggest that processes shaping early vulnerability for later mental disorders arise well before conception. There is an emerging case for expanding developmental theories and trialling preventive interventions in the years before pregnancy.